Price Setting and Competition in a Simple Duopoly Model - Gale, Douglas (Quarterly Journal of Economics, 1988)
The paper studies a market in which there are two sellers and one buyer. Each agent wants to trade at most one unit of an indivisible commodity. The sellers are uncertain whether the buyer is receiving offers from one or both of them at any given time. This model induces competitive and monopolistic outcomes for particular parameter values. But, other things being equal, as the buyer becomes very patient, the equilibrium price converges to the competitive one.